2020
DOI: 10.1002/cti2.1130
|View full text |Cite
|
Sign up to set email alerts
|

Defective formation of IgA memory B cells, Th1 and Th17 cells in symptomatic patients with selective IgA deficiency

Abstract: Objective. Selective IgA deficiency (sIgAD) is the most common primary immunodeficiency in Western countries. Patients can suffer from recurrent infections and autoimmune diseases because of a largely unknown aetiology. To increase insights into the pathophysiology of the disease, we studied memory B and T cells and cytokine concentrations in peripheral blood. Methods. We analysed 30 sIgAD patients (12 children, 18 adults) through detailed phenotyping of peripheral B-cell, CD8 + T-cell and CD4 + Tcell subsets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…They were increased in patients with severe SIgAD as compared to those with mild severity [166]. Increased level of CD21low was previously described but without correlation to clinical status [167].…”
Section: Iga Deficiency and Cvidmentioning
confidence: 64%
“…They were increased in patients with severe SIgAD as compared to those with mild severity [166]. Increased level of CD21low was previously described but without correlation to clinical status [167].…”
Section: Iga Deficiency and Cvidmentioning
confidence: 64%
“…Intrinsic B-cell defects, T cell, cytokine network abnormalities and environmental factors (including the microbiome composition) have all been associated with IgA deficiency. [25][26][27][28][29] While no clear inheritance pattern had been described, several monogenic mutations have been associated with IgA deficiency. 30 Also, multiple HLA and non-HLA genes have been described to be associated with disease phenotypes and development.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of IgA deficiency represents a heterogeneous group of abnormalities. Intrinsic B‐cell defects, T cell, cytokine network abnormalities and environmental factors (including the microbiome composition) have all been associated with IgA deficiency 25–29 . While no clear inheritance pattern had been described, several monogenic mutations have been associated with IgA deficiency 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In SIgAD patients a reduction in IgA+ memory B cells was found associated with no defect in class switching and affinity maturation. Therefore, it is suggested that SIgAD patients have defective regulation of the IgA response due to reduced Th1 and Th17 cells and increased blood concentrations of TGF-β1, BAFF and APRIL ( 137 ). In addition, increased numbers of CD27+IgA+ memory B cells were found in a cohort of children (n=729) having ever showed a food allergic reaction over the first 10 years of their life.…”
Section: Pathogenesis Of Sigadmentioning
confidence: 99%